Supporting Postsecondary English Language Learners’ Writing Proficiency Using Technological Tools - Moore, Kathleen A.; Rutherford, Camille; Crawford, Keith A. (Journal of International Students, 2016)
Postsecondary international students who are also English language learners face a number of challenges when studying abroad and often are provided with services to support their learning. Though some research examines how institutions can support this population of students, few studies explore how technology is used to support language development and writing proficiency. This article reports on an exploratory study that examined the resources English language learners use to support their writing and the impact of the use of writing productivity software’s on writing proficiency. Data were collected using a survey, writing samples, and a focus group. Findings indicate students frequently use technological tools to enhance learning and that technology-based supports such as writing productivity software can complement face-to-face supports.